PERSPEKTIF PENDIDIKAN HUMANISTIK PADA “PATA DELA” ORANG BAJAWA DI FLORES BAGIAN TENGAH - Gregorius Sebo Bito (Program Studi PGSD Universitas Flores, 2024)
Both culture and education have an impact on one another; on the one hand, the cultural background shapes the educational system, and on the other, education helps spread cultural norms and values. The purpose of this study is to investigate how the humanistic educational ideas put out by Abraham Maslow and Carl Rogers relate to the ideals found in pata dela, an intangible cultural heritage of the Bajawa people. The researcher's experience as a Bajawa community member served as the basis for data gathering in this qualitative study, which was validated by literary sources. This study's primary focus is oral transmission of pata dela, and it analyzes this by relating its values to the notion of humanistic education. The results of the study show that Maslow's theory of basic needs and self-actualization are pertinent to the ideals found in pata dela. In keeping with the ideas put out by Rogers, pata dela also highlights the value of empathy and healthy social relationships. As a result, pata dela can be an important teaching tool that combines cultural and contemporary educational ideas. This study highlights how pata dela values can support the growth of culture-based education and enhance humanistic education theory.